Growing Up in Ireland. (1st October 2019) - McNamara, Eoin; Murray, Aisling; Williams, James
Abstract : Growing Up in Ireland (GUI) is a two-cohort, longitudinal study of children and young people. The study aims to describe the health and development of Irish children across a range of topics; these include physical and mental health, family socio-demographic status, education, and the child's behaviour, attitudes and key relationships. The study has been collecting data since 2007, beginning with a child cohort at nine years old (n = 8, 568) and then an infant cohort at nine months old (n = 11, 134). These data provide researchers and policy makers with a unique analytical tool to explore the well-being of children in Ireland. This paper provides an overview of all the stages involved in the development of the study, from its inception, to the establishment of the study's aims, objectives and design, the ongoing data collection and panel maintenance, and the many uses of GUI data today.